Hardware-Software and Metrological Support of Drones - Zeng, Xinyu (Національний університет «Львівська політехніка», 2025)
This dissertation focuses on the research, development, and implementation of advanced soft and hardware systems used in drones, with a particular emphasis on metrological support for their performance optimization. A significant part of the dissertation is devoted to ensuring the accuracy and reliability of measurements in drone operations through advanced calibration techniques and testing platforms, due to the drone’s ability to perform autonomously with a high degree of precision in various environments.
Keywords: drone, hardware, software, metrological support, control, uncertainty, error, sensor calibration, hydrodynamic modeling and simulation, filtering algorithms, underwater robotics, performance assessing; 681.5